PENGARUH SEKTOR PARIWISATA TERHADAP KEMANDIRIAN FISKAL DAERAH KABUPATEN PACITAN (PASCA PENETAPAN KAWASAN GEOPARK GUNUNGSEWU) - Annisa, Rosalina Nur; Salindri, Yerika Ayu (Kepariwisataan: Jurnal Ilmiah, 2018)
In the management of tourism sector, Pacitan regency can not be separated from the role of central government in meeting the economic needs and tourism infrastructure in Pacitan regency. The policy of regional autonomy has encouraged the Pacitan local government to manage its own finances in order to increase the regional fiscal independence. The research sample is district government of Pacitan determined by purposive sampling method. The method of analysis in this study is to use simple linear regression analysis. The analysis used is classical assumption test and simple linear regression analysis is used to know the influence between independent variable (X) that is tourism sector to dependent variable (Y) that is fiscal independence. From the results of research proved that the tourism sector positively affect the fiscal independence of the region Pacitan post-establishment of Geopark Gunungsewu. Keywords: Tourism Sector, Fiscal Independence, Geopark Gunungsewu